Conditional Knockout of Breast Carcinoma Amplified Sequence 2 (BCAS2) in Mouse Forebrain Causes Dendritic Malformation via β-catenin - Huang, Chu-Wei (Sci Rep, 2016)
Breast carcinoma amplified sequence 2 (BCAS2) is a core component of the hPrP19 complex that controls RNA splicing. Here, we performed an exon array assay and showed that β-catenin is a target of BCAS2 splicing regulation. The regulation of dendrite growth and morphology by β-catenin is well documented. Therefore, we generated conditional knockout (cKO) mice to eliminate the BCAS2 expression in the forebrain to investigate the role of BCAS2 in dendrite growth. BCAS2 cKO mice showed a microcephaly-like phenotype with a reduced volume in the dentate gyrus (DG) and low levels of learning and memory, as evaluated using Morris water maze analysis and passive avoidance, respectively. Golgi staining revealed shorter dendrites, less dendritic complexity and decreased spine density in the DG of BCAS2 cKO mice. Moreover, the cKO mice displayed a short dendrite length in newborn neurons labeled by DCX, a marker of immature neurons, and BrdU incorporation. To further examine the mechanism underlying BCAS2-mediated dendritic malformation, we overexpressed β-catenin in BCAS2-depleted primary neurons and found that the dendritic growth was restored. In summary, BCAS2 is an upstream regulator of β-catenin gene expression and plays a role in dendrite growth at least partly through β-catenin.